A component abstraction for business processes. (1st January 2012) - Barat, Souvik; Kulkarni, Vinay
With continued increase in business dynamics, it is becoming increasingly harder to deliver purpose-specific business system in the ever-shrinking window of opportunity. As business systems for the same intent tend to be similar but never the same, they have considerable overlap with well-defined differences. Software product line engineering techniques attempt to address this problem for software artefacts. Separation of business process concerns from application functionality, as advocated in process centric application development, demands solution on similar lines for business processes too. To this effect, we propose an abstraction for business processes that addresses composition, variability and resolution in a unified manner. We present the abstraction, its model-based realisation, and illustration with an example.